Interest rate smoothing in the face of energy shocks - Stefano Maria Corbellini (University of Bern, Department of Economics, 2025)
This paper analyzes the monetary policy trade-off between defending purchasing power of consumers and keeping moderate debt cost for borrowers, in the framework of a heterogeneous agent New Keynesian open economy hit by a foreign energy price shock. Raising the interest rate indeed combats the loss in purchasing power due to the energy shock through a real exchange rate appreciation: however, this comes at the expense of higher interest payments for debtors. The trade-off can be resolved by adopting a milder interest rate policy during the crisis in exchange for a prolonged contraction beyond the energy shock time span. This interest rate smoothing approach allows to still experience a real appreciation today, while spreading the impact on debt costs more evenly over time. This policy counterfactual is analyzed in a quantitative model of the UK economy under the 2022-2023 energy price hike, where the loss of consumers' purchasing power and the vulnerability of mortgage costs to higher policy rates have been elements of paramount empirical relevance.
Keywords: 330